'I'm not just a number on a sheet, I'm a person': Domiciliary care, self and getting older. (12th December 2019) - Hughes, Suzanne; Burch, Sarah
Abstract: Social care funding is reducing in spite of a growing older population. Within this context, domiciliary services are increasingly failing to deliver care that respects the individuality and heterogeneity of older people. To date, there has been limited research in the U.K. that explores, from the older person's perspective, how care practices interact with self. Using biographical‐narrative methodology, this study takes a constructionist approach to understand the individual's lived experience of care and how it interacts with sense of self. A three‐stage model of data collection was used, beginning with a narrative biographic enquiry, exploring with participants (65 yrs +, n  = 17) their journeys into care and any possible relationship to personal identity. Stage 2 involved a two‐week period of diary completion, with participants recording daily reflections on their care experiences. In stage 3, a semi‐structured interview explored the diary entries, linking back to the narrative biographic enquiry to reveal ways in which specific care practices interacted with the sense of self. The findings reveal that a strong relationship between older person and formal carer, forged through familiarity, regularity and consistency, plays a significant role in promoting feelings of autonomy. Furthermore, such relationship mediates against the loss of executional autonomy that often accompanies increasing disability. Maintaining autonomy and control was a recurring theme, including in relation to home, privacy and dignity. Feelings of autonomy are also promoted when formal carers understand the unique ways in which individuals experience ageing and being in the cared‐for relationship. This paper suggests that a care approach should be based on two tenets. First, a knowledge and insight into the importance of understanding and respecting the older person's continuing development of self, and second applying this knowledge to care through a positive, stable and consistent relationship between the older person and the carer.